2006
DOI: 10.1542/peds.2005-0413
|View full text |Cite
|
Sign up to set email alerts
|

Achieved Versus Intended Pulse Oximeter Saturation in Infants Born Less Than 28 Weeks' Gestation: The AVIOx Study

Abstract: Success with maintaining the intended pulse oximeter saturation range varied substantially among centers, among patients within centers, and for individual patients over time. Most noncompliance was above the intended range. Methods for improving compliance and the effect of improved compliance on neonatal outcomes require additional research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
157
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 19 publications
11
157
1
Order By: Relevance
“…Most closed loop studies compared automated to routine clinical care (14,21,(24)(25)(26), only one study could show a significant improvement comparing closed loop to dedicated manual control (22). In addition, in our study, alarm range was equal to target range, which created an ideal setting for dedicated manual control as caregivers are more effective in keeping SpO 2 within alarm limits then within target limits in preterm infants (32). Interestingly, our data suggest that keeping animals manually within the limits was more difficult with high oxygen need, while individual oxygen need did not influence the performance of the automated control.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Most closed loop studies compared automated to routine clinical care (14,21,(24)(25)(26), only one study could show a significant improvement comparing closed loop to dedicated manual control (22). In addition, in our study, alarm range was equal to target range, which created an ideal setting for dedicated manual control as caregivers are more effective in keeping SpO 2 within alarm limits then within target limits in preterm infants (32). Interestingly, our data suggest that keeping animals manually within the limits was more difficult with high oxygen need, while individual oxygen need did not influence the performance of the automated control.…”
Section: Discussionmentioning
confidence: 81%
“…The average number of adjustments during resuscitation was similar in both groups (median 27, IQR (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) vs. 28 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36); P = 0.796). (Figure 1b), however the oxygen need was highly variable in both the automated (IQR (0.52-0.98)) and the manual group (IQR (0.37-0.72)).…”
Section: Resuscitationmentioning
confidence: 92%
“…12 Studies that compare actual versus intended pulse oxygen saturation in very preterm infants have shown that poor compliance with the desired range of oxygen saturation target values and with alarm limits for pulse oximetry is an important and common problem in NICUs worldwide. [13][14][15][16][17] However, our neonatal team has maintained COT study participants within the intended pulse oximetry alarm limits between 68 and 79% of the time. Although our teams' performance is among the best of all neonatal units participating in the COT study, it needs to be highlighted that we only measured compliance during the first 3 days of life while infants were receiving supplemental oxygen.…”
Section: /41mentioning
confidence: 99%
“…However, a multicenter study that measured compliance during the first 4 weeks of life found no significant association of the target range compliance with chronological age, mechanical ventilator status, pulmonary acuity score, birth weight and severity of illness at birth. 13 Nevertheless, when discussing the results of oxygen saturation studies, it should be done in respect of the duration of the monitoring. Hagadorn et al 13 prospectively compared the achieved SpO 2 with the intended range in a cohort of 84 infants, <28 weeks gestation, during the first 4 weeks of life in 14 centers and three countries.…”
Section: /41mentioning
confidence: 99%
See 1 more Smart Citation